Degradation mechanisms of geosmin and 2-MIB during UV photolysis and UV/chlorine reactions. (November 2016) - Kim, Tae-Kyoung; Moon, Bo-Ram; Kim, Taeyeon; Kim, Moon-Kyung; Zoh, Kyung-Duk
Abstract: We conducted chlorination, UV photolysis, and UV/chlorin reactions to investigate the intermediate formation and degradation mechanisms of geosmin and 2-methylisoborneol (2-MIB) in water. Chlorination hardly removed geosmin and 2-MIB, while the UV/chlorine reaction at 254 nm completely removed geosmin and 2-MIB within 40 min and 1 h, respectively, with lesser removals of both compounds during UV photolysis. The kinetics during both UV photolysis and UV/chlorine reactions followed a pseudo first-order reaction. Chloroform was found as a chlorinated intermediate during the UV/chlorine reaction of both geosmin and 2-MIB. The pH affected both the degradation and chloroform production during the UV/chlorine reaction. The open ring and dehydration intermediates identified during UV/chlorine reactions were 1, 4-dimethyl-adamantane, and 1, 3-dimethyl-adamantane from geosmin, 2-methylenebornane, and 2-methyl-2-bornene from 2-MIB, respectively. Additionally, 2-methyl-3-pentanol, 2, 4-dimethyl-1-heptene, 4-methyl-2-heptanone, and 1, 1-dichloro-2, 4-dimethyl-1-heptane were newly identified intermediates from UV/chlorine reactions of both geosmin and 2-MIB. These intermediates were degraded as the reaction progressed. We proposed possible degradation pathways during the UV photolysis and UV/chlorine reactions of both compounds using the identified intermediates. Graphical abstract: Highlights: We newly identified four intermediates from UV/chlorination of both geosmin and 2-MIB. Combined UV/chlorine reaction completely degraded both odorants and intermediates. Chloroform was observed as a main chlorinated byproduct from UV/Cl2 reaction. Removals of geosmin and 2-MIB and chloroform production were affected by pH. The degradation pathways of UV/chlorination of geosmin and 2-MIB were proposed.